Rapid growing mass of the mandible due to an oral metastasis of thymoma: Case report of an extremely rare localization and review of published cases - Francesco Scilla; Cosimo Rupe; Gioele Gioco; Luca Raffaelli; Filippo Lococo; Ciro Mazzarella; Guido Rindi; Romeo Patini; Carlo Lajolo (Heliyon)
Background: Cancer metastases in the oral cavity are relatively uncommon, occurring in approximately 1–3% of malignant cases. Thymomas and thymic carcinomas are the two main tumors that can affect the thymus, a lymphatic gland that plays an important role in regulating the immune system. The aims of this paper are (i) to describe an extremely rare case of thymoma metastasis to the oral cavity (ii) report all published cases of thymic tumor metastases to the oral cavity. Case report: A 62-year-old Italian male patient was referred to the Oral Medicine Department at the Fondazione Policlinico Universitario A. Gemelli – IRCCS, Rome to evaluate a rapidly growing, non-ulcerated swelling in the left buccal mucosa. After clinical examination and radiological examination, an incisional biopsy was performed under local anesthesia. Thus, a final diagnosis of intraoral metastasis of thymoma was achieve.A review of the literature of oral metastases due to thymic tumor was also conducted through a systematic search in accordance with PRISMA guidelines, via PubMed, Scopus and CENTRAL engines. Out of 328 articles retrieved, only two articles reported oral metastasis of thymic tumors; and two reports of ectopic thymic carcinoma of the parotid gland were found. Conclusions: This paper provides a rare case of oral metastasis of thymoma. The present paper reports an almost undescribed condition. Future reports will be useful in increasing knowledge regarding this area. The oral screening of patients with thymic tumors could be useful, considering the relationship between these diseases and oral disorders.